PROSES BERPIKIR SISWA TUNAGRAHITA RINGAN DALAM MEMECAHKAN MASALAH MATEMATIKA BENTUK SOAL CERITA PADA OPERASI HITUNG CAMPURAN - Muhlishotul Hidayah; Imam Sujadi; Pangadi Pangadi (Journal of Mathematics and Mathematics Education, 2014)
Abstract: The aim of this research was to describe the thinking process of students with mild mental retardation in solving mathematics problems concerning with story questions in a mixed arithmetic operation. This research was a qualitative case study. The subjects of this research were the students of VIII C SLB Negeri Surakarta consisting of two students: a male and a female students. The procedure of selecting the subject used purposive sampling. The data of the research were collected by using think aloud method. To validate the data, the researcher used time triangulation. The techniques of analyzing the data were: (1) classifying the data into four categories based on Santrock steps: (a) finding and framing the problem, (b) developing problem-solving strategies, (c) evaluating solutions, and (d) rethinking and redefining the problem and solutions, and then reducing the data that are not included in four categories, (2) presenting the data in table, and (3) concluding thinking process of students with mild mental retardation in each category. The results of the research showed that: (a) finding and framing the problem: The two students began the activities by reading the questions, then the students kept silent while reexamining the questions, the students could not mention what was known and what was asked, the students waited for the instruction about what to do, the students could only reveal some information on what was known. To find out the information asked, the one of students got difficulty in mentioning what was asked shown by silent respond then read the questions again, and another student reexamined the questions and revealed the answers related to arithmetic operations. In framing the problem-solving strategy, these two students needed guidance to make strategy by linking the arithmetic operations, and another student also expresses problem-solving strategies that were not appropriate on the first step, (b) developing problem-solving strategies: these two students needed guidance in solving problems, another student solved problems based on the strategy that had been compiled by linking the arithmetic operations, while another student got difficulties when implementing different strategies. In the process of calculating, the students completed the calculation by compiling it downwards, and the students tended to use their hands as a means of calculation, (c) evaluating solutions: the student checked the answer by recalculating the answer, while another student only looked the answer at glance and believed in the answer, (d) rethinking and redefining the problems and solutions: these two students looked at the answer and revealed that no other idea/way in solving the problem.Key words: thinking process, mild mental retardation, problem solving, story questions.